NORMATIVE STUDY ON THE HARMONIZATION OF STANDARDS IN INTERNATIONAL CIVIL AGREEMENTS ON THE INTEGRATION OF HALAL CERTIFICATION AND BUSINESS CONTRACTS IN THE INDONESIAN HALAL HUB SYSTEM - J.E. Melky Purba (PT. Sinergi Legal Publisher, 2025)
The dominance of the global halal narrative is no longer solely determined by religious credibility, but also by legal certainty and international legal standards. Amidst the booming global halal industry, valued at trillions of dollars, Indonesia remains mired in recognition ambiguity and fragmented standards. The country with the world's largest Muslim population should not only be a market, but a pioneer and determinant in the international halal system. Ironically, Indonesia's halal certification issued by the BPJPH (Indonesian Halal Product Regulatory Agency) is still not fully recognized by many strategic trading partners. When cross-border business contracts include halal assurance as an essential clause, the lack of harmonization of standards between countries opens the door to disputes, breaches of contract, and even immeasurable reputational and economic losses. This research uses a normative juridical approach supported by the theory of contractual obligations and the theory of international legal harmonization to systematically examine how the integration of halal standards can be implemented in cross-border business contracts, as well as the forms of civil legal liability in the event of default due to non-compliance with halal standards. The main findings indicate that without a mutual recognition mechanism explicitly outlined in a contractual clause, the halal guarantees included in the agreement will be merely empty promises lacking legal enforcement. The Indonesian Halal Hub will never become a strategic reality if the government continues to play it safe and passive in global harmonization forums. Instead, aggressive political-legal measures are needed, starting from strengthening bilateral agreements, constructing robust contractual clauses, and international advocacy towards the birth of a multilateral treaty on the unification of binding halal standards. Without this, Indonesia will simply be a rubber stamp, not an architect of the global halal system.